Seasonal drivers of picoeukaryotic community structure and assembly in complex aquatic systems: A case study of the Changjiang (Yangtze) River Estuary and East China Sea - Ran Li; Wenxin Fan; Xianghui Guo; Yan Bai; Ping Sun; Nianzhi Jiao; Dapeng Xu (Marine Pollution Bulletin, 2026)

Out-of-Plane bending behavior of a novel double steel plate concrete Composite-New tubular roof structure - Liang Yue; Yue Yang; Yi-Ran Liang; Li-Yan Xu; Jie Xu; Chen Wang (Tunnelling and Underground Space Technology, 2026)

Turbulence-induced detachment of fine particles from bubble surfaces and associated flow field characteristics - Hailing He; Zhixin Sun; Xiaoheng Li; Xiaokang Yan; Lijun Wang; Haijun Zhang; Li Lin; Jincai Ran (Minerals Engineering, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

An ultrathin triazine-anchored hypercrosslinked and nonflammable solid polymer electrolyte for safe Li metal batteries - Ran Wang; Yongle Yan; Zelin Lv; Xiaoxiao Li; Xutao Liang; Yang Gao; Mengchao Li; Lifeng Hou; Shi Wang; Zhong Jin; Qian Wang (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Al-modified ReS2/TiO2 with enhanced adsorption and stepwise interfacial charge migration for photocatalytic PFOA removal - Ran Chen; Feng Liu; Zhenkai Liu; Jun Wan; Qidi Liu; Yixin Ma; Yan Li; Shunli Wan; Yongming Luo; Haijiao Xie (Journal of Environmental Chemical Engineering, 2026)

Cyanidin chloride activates mitophagy to delay aging via PINK1/parkin pathway - Zhaotun Hu; Yan Ran; Xiaocong Li; He Zha; Yi Xiao (Food Research International, 2026)

Multi-scale analysis of patterns, risks, and mechanisms of edaphic antibiotic resistance genes on the Qinghai-Tibet Plateau: Integrating regional and national perspectives - Weiguo Zhang; Guangcan Ran; Pengfu Li; Junxian Ke; Shenyang Ji; Yan Gao; Rongjun Bian; Zhi Wang (Environmental Pollution, 2026)

Three-dimensional level set-based topology optimization using the adjoint method for a tee flow equalizer with a low-pressure-loss uniform air supply - Yan Tian; Ran Gao; Yi Wang; Angui Li; Xinpeng Hao; Hui Guo; Liwei Tian (Building and Environment, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Tailored micro-encapsulation for food technology: A review on the fabrication and application of core-shell microcapsules - Ran Tu; Jiawang Jin; Yan Li; Chenggang Deng; Qinhong Wang (Trends in Food Science & Technology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Identification of gas-liquid flow patterns in horizontal pipes using phase fraction-integrated physics-guided neural network - Yan Zhang; Jie Pan; Liangliang Wang; Wei Liu; Yeqi Cao; Ran Li; Wujie Wang; Feiyue Han (Ocean Engineering, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Regulating the hydrogen transfer pathways for electrochemical nitrate-to-ammonia at industrial current density - Zeyu Li; Zichen Shi; Chu Zhang; Chunshuang Yan; Shijie Chen; Nian Ran; Chenhui Yin; Qingyu Yan; Chade Lv (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

A simple method to estimate seismic subsidence in soft soil under amplitude non-stationary seismic action - Gan-Ling Xian; Jing-Yan Lan; Li-Chun Chen; Yong-Zhi Wang; Lei Wang; Zhao-Ran Wu (Engineering Geology, 2026)

Effects of salinity management practices on the soil organic carbon stock in China's salinized soils: A meta-analysis - Wenchao Zhang; Ran Li; Yangyang Sun; Zhentao Sun; Shujuan Wang; Jia Liu; Yan Li; Lizhen Xu; Yonggan Zhao (CATENA, 2026)

Simulation-Based Maritime Scheduling Optimization for Bidirectional Ship Flow in Multi-Chamber Lock Systems: Incorporating Chamber Operations for Efficient Management - Nini Zhang; Xin Li; Wen Xie; Sudong Xu; Weikai Tan; Cheng Cheng; Ran Yan (Journal of Marine Science and Engineering, 2026)
This paper addresses the bidirectional multi-chamber lock scheduling problem by formulating a multi-objective mixed-integer linear programming (MILP) model that simultaneously minimizes average ship waiting time and maximizes chamber utilization. A tailored adaptive large neighborhood search (ALNS) algorithm is developed specifically based on the principle of the destruction and reconstruction of solutions. The algorithm efficacy is validated using the real-word data from Huai’an Lock of the Subei canal. The scheduling rules and parameters are defined from practical operation records. Simulation results demonstrate that the ALNS-based optimization significantly improves lock performance with average chamber utilization increasing by 12.98% and waiting time decreasing by 44.40%. Sensitivity analyses on objective weights further confirm the robustness of the proposed method. Benchmark comparisons with a greedy heuristic, genetic algorithm (GA), and particle swarm optimization (PSO) highlight the effectiveness and computational efficiency of ALNS. This study further explores a threshold-based directional control strategy, showing that relaxing strict alternating-direction rules under asymmetric traffic demand can improve efficiency. The findings provide practical insights for lock scheduling, offering decision support for lock authorities in designing adaptive scheduling and directional control policies.

An Experimental Investigation on the Effect of Aspect Ratio on the Flow-Induced Motion and Energy Harvesting of a Circular Cylinder with T-Shaped Attachments - Danjie Ran; Yizhuo Wu; Bomeng Feng; Kainan Chen; Xiang Yan; Wene Wang; Jijian Lian; Shishen Li (Journal of Marine Science and Engineering, 2026)
Water channel experiments were conducted to investigate the influence of aspect ratio (H/D = 0.9–1.9) on the flow-induced motion (FIM) and hydrokinetic energy conversion performance of an elastically mounted circular cylinder with T-shaped attachments (Cir-T-Att). The results indicate that the aspect ratio critically governs the vortex-induced vibration (VIV) to galloping transition by modulating the effective angle of attack. While larger H/D promotes galloping and higher amplitudes under low damping, this benefit is negated under elevated system damping, where amplitudes are uniformly suppressed. Consequently, the maximum power output exhibits a non-monotonic dependence with H/D. Within the investigated parametric range, peak performance occurs at H/D = 1.1, with a total damping ratio ζtotal = 0.122 and reduced velocity Ur = 11.25. For practical harvester design, the optimal H/D should be selected by aligning the intended oscillation regime with local flow characteristics.

Exogenous microbial inoculation drives alpine compost maturity by overcoming thermodynamic barriers and reshaping fungal networks - Zongcheng Cai; Fayi Li; Hu Yan; Shancun Bao; Hairong Zhang; Shouquan Fu; Ran Qin; Enqi Yang; Quanfang Lei; Jianjun Shi (Journal of Environmental Chemical Engineering, 2026)

Whole-genome analysis of a polyvalent Salmonella phage reveals its potential to combat intracellular infection and food contamination - Liting Wu; Penghui Li; Mei Bai; Ning Zhu; Zhenyu Wang; Qiuchun Li; Hongduo Bao; Bukola Onarinde; Yan Zhou; Ran Wang; Hui Zhang (Food Research International, 2026)

W/O/W emulsion-filled egg white gel co-stabilized by protein and γ-cyclodextrin MOFs with multi-chamber encapsulation potential - Chan Li; Xue Yang; Yunfei Zou; Li Zhang; Chuhuan Wei; Yan Ran; E Zhao; Jibiao Yuan; Keshan Wang; Yongguo Jin; Ying Zhou; Qiujin Zhu; et al. (Food Research International, 2026)

Unveiling the hidden threat of chlorinated organic pollutants residual in anaerobic conditions: A regional multi-habitat perspective - Shuyao Li; Yifan Song; Ran Bao; Wei Wang; Jiachun Shi; Chaofeng Shen; Jianming Xu; Yan He (Journal of Hazardous Materials, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Energy–vortex–momentum coupling bridges hydrodynamics and mass transfer of perfluoroalkyl acids - Yixin Ma; Zulin Hua; Limei Zhong; Shunli Wan; Yan Li; Ran Chen; Qidi Liu (Environmental Pollution, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Deglycosylated alfalfa saponins enhance antioxidant capacity and gene expression in obese mice - Ran Zhang; Zhumei Du; Zhiwei Li; Yuxi Feng; Xuebing Yan (Natural Product Research, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Analysis of the resistance and flow characteristics of a square diffuser under adjacent influence conditions based on design of experiments - Haimeng Li; Wei Xu; Ran Gao; Xinyu Zhang; Chi Zhang; Yan Tian; Yi Wang; Ruoyin Jing (Building and Environment, 2026)

Low-temperature mineral engineering stabilizes anchored cobalt sites for ultrafast antibiotic destruction via electron transfer-driven radical/nonradical synergy - Liyao Ren; Ran Liu; Runbin Zeng; Lingling Cao; Wenyu Wang; Xuguang Li; Xing Xu; Yanxia Zhao; Liangguo Yan; Yanfei Li; Wen Song (ENGINEERING Environment, 2026)

Safe nitrogen boundaries for sustainable pomelo production: A case study in the hilly regions of southern China - Ziwei Luo; Ran Li; Xiaotong Hu; Yedong Liu; Zhiyuan He; Ruixiang Yang; Zhixiong Zeng; Yingzhe Zeng; Bingkun Lu; Xiaojun Yan; Liangquan Wu (Agriculture, Ecosystems & Environment, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Dual-motor control of a flow-induced motion energy conversion system: Device development and experimental validation - Danjie Ran; Kainan Chen; Xiang Yan; Zuhao Zhang; Wene Wang; Yuanchun Qi; Xu Yang; Zhenyu Li (Ocean Engineering, 2026)

Hierarchical carbon electrocatalysts with atomic Co-N/Pyridinic-N synergy for efficient bifunctional oxygen reactions - Jian Li; Zongqi Zhao; Xinxin Pi; Guangshun Chai; Lingtao Ran; Chunlei Zhang; Yanhui Li; Junhan He; Keke Zhang; Yan He (Fuel, 2026)

An optimized shared responsibility accounting framework: unveiling the big black shadows behind small emitters in global value chains - Xiyuan Li; Ran Wang; Yang Zhou; Yunfeng Yan; Jinjun Xue; Zhongxiu Zhao (Ecological Economics, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Alkali promotion in nonmetallic boron-based catalysts: Establishing structure–activity correlations for selective methane oxidation - Ran Yan; Penghui Li; Siyu Liu; Xindi Zhang; Leisu Li; Chenxin Zhang; Shaolong Wan; Jingdong Lin; Xiaodong Yi; Lingtao Liu; Shuai Wang (Chemical Engineering Journal, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Constructing an integrated photocatalytic-Fenton-like system for rapid sterilization by S-scheme SCN@CuS heterojunction with manipulated charge dynamics and activated H2O2 - Mingzhu Yuan; Ran Qiu; Weile Xie; Yan Ke; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Qinghua Liu; Xiangang Lin (Chemical Engineering Journal, 2026)

CD33 Isoform Splicing Dysregulation: A Molecular Determinant of Microglial Dysfunction in Alzheimer’s Disease Pathology - Xiao-Yan Li; Yu Zhang; Zhao Ran; Jia-Xin Luo; Xiao-Qin Yu; Mei-Hong Lu (Molecular Neurobiology, 2026)

A two-stage ship path planning method based on trial maneuvers - Yangyu Zhou; Shuxiu Liang; Qiaofeng Ma; Qingren Xue; Jia Li; Ziyu Deng; Ran Yan (Ocean Engineering, 2025)

Alterations in the profiles of rumen microbiota and metabolites in Holstein and Jersey dairy cows under heat stress - Yuan Li; Ran Yu; Shujing Tan; Longwei Sun; Yexiao Yan; Junpeng Huang; Muhammad Huraira Waseem; Zhenjiang Wang; Chengmin Li (Journal of Thermal Biology, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Recovery of V2O5 from spent catalysts for NH3 and humidity sensors - Yan Li; Ping Hu; Miaomiao Liu; Bo Ran; Yuqing Zhu; Junxi Cheng; Jun Sun; Zhaofeng Wu (Journal of Environmental Chemical Engineering, 2025)

Design of Ni-MOF@biochar heterostructures via ligand-induced distortion for highly selective N2H4 sensing - Bo Ran; Ping Hu; Jun Sun; Jialu Fang; Yan Li; Qihua Sun; Zhizhong Zhang; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

Unraveling the crucial role of UPR pathway in rat brain development - Yan Jiang; Ajun Wang; Nian Zou; Huimin Dai; Ran Shan; Siyu Ren; Tongcui Jiang; Nan Li (Molecular Biology Reports, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

Stirring enrichment/bio-proliferation dual-amplified photoelectrochemical phage biosensor for selective and sensitive detection of foodborne pathogens - Yuqi Zhang; Liu Liu; Tianhua Li; Rouyi Gao; Wenhao Dong; Yan Bai; Lingman Ran; Suying Gu; Zhenzhong Yu; Jincan He; Ning Gan (Analytica Chimica Acta, 2025)

Nitrite exposure on gills of Oreochromis niloticus: structure change, immune response, and apoptosis - Chaowei Song; Tiansheng Zhu; Ran Cai; Yang Yu; Ziyan Liu; Jianing Yan; Yingying Lian; Jiaqi Li; Wensheng Li (Frontiers in Marine Science, 2025)
Nitrite is one of the most common pollutants in high-density aquaculture systems and has a potentially serious impact on the health of fish. The gill, as the organ directly in contact with the environment, performs several vital physiological functions, including gas exchange, osmotic pressure regulation, and mucosal immunity. Using a series of nitrite concentration gradients, we investigated the impact of nitrite on tilapia gills, with a focus on its immune responses. The results indicated that nitrite exposure could significantly increase the number of mucus cells and change the subtypes of chloride cells. Nitrite exposure significantly elevated serum catalase (CAT) activity and decreased superoxide dismutase (SOD) activity. After nitrite treatment, the expression of ion channel protein genes was markedly affected, with a substantial increase in Na + /Cl − cotransporter ( ncc ) expression. Inflammatory gene expression in the gill was also significantly altered. Both in vitro and in vivo experiments revealed that key genes in the IL-17 signaling pathway were considerably altered after nitrite exposure. Mitochondrial damage and apoptosis in the gill tissues were also found after nitrite exposure. In conclusion, nitrite exposure altered immune function and ion transport, especially the activation of the IL-17 signaling pathway, damage to mitochondrial structure, and apoptosis in the gill. This study enhances our understanding of the mechanisms underlying nitrite-induced damage to the gill.

Large-scale single tree information extraction of oil palm in Malaysia based on sub-meter visible light satellite images - Sen Zhang; Nan Li; Yaoping Cui; Jinwei Dong; Le Yu; Lishan Ran; Ziyue Chen; Jiqiang Niu; Wei Yan; Kasturi Devi Kanniah; Xiangming Xiao (Computers and Electronics in Agriculture, 2025)

Bi-modal synergistic hydrogel sensors coupled with machine learning enable gesture parsing and identity recognition - Bihai Yang; Yuwen Li; Kai Zheng; Yan Xiong; Xiaokun Jin; Lixian Zhu; Ran Cai; Bin Hu (Chemical Engineering Journal, 2025)

Lipidomic profiling of cutaneous surface lipid alterations in sensitive scalp in Beijing - Ran Li; Qian Jiao; Liya Song; Youjie He; Huaming He; Cheng Zhou; Yan Jia (Chemistry and Physics of Lipids, 2025)

FiVOS: A fish segmentation algorithm based on interactive video object segmentation and filter enhancement - Yuqing Duan; Song Zhang; Shili Zhao; Xiaoyi Gu; Yan Meng; Daoliang Li; Ran Zhao (Computers and Electronics in Agriculture, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Synergistic effect of dual vacancies and interface structure enables 100 % CH4 selectivity for CO2 photoreduction - Jing Tian; Wenjuan Li; Weiguang Ran; Yuhua Wang; Kuanchang Liu; Na Li; Tingjiang Yan (Chemical Engineering Journal, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Targeted air supply to the working area of a tall plant based on the principle of fluid topology optimization - Hongchen Li; Dongzheng Wang; Min Zhou; Yonghong Jia; Yan Tian; Yang Xuan; Yafan Jin; Ran Gao (Building and Environment, 2025)

Study on the resistance calculation method for ventilation duct systems under non-fully developed flow conditions - Yi Wang; Sen Yang; Ran Gao; Yan Tian; Ruoyin Jing; Angui Li (Building and Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Unsteady hydrodynamic performance of a submarine with a new kind of pump-jet propulsor - Yun Ding; Xin-ran Li; Wen-Quan Wang; Guanzhe Cui; Tao Guo; Yan Yan (Ocean Engineering, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

A two-level turbulent density-based topology optimization method: A low-resistance U-bend channel flow - Yan Tian; Ran Gao; Yi Wang; Angui Li; Xin Dong; Tong Li; Shengrui Yu (Building and Environment, 2025)

Morphological and physiological responses to aridity in narrowly- and widely-distributed plant species in drylands - Junlan Xiong; Weigang Hu; Allan Degen; Jie Peng; Longwei Dong; Li Yan; Qingqing Hou; Shuran Yao; Ying Sun; Xiaoting Wang; Yahui Zhang; Yan Deng; et al. (Science China Life Sciences, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Seasonal migration dynamics of the rice leaf folder Cnaphalocrocis medinalis across the South China Sea - Xianyong Zhou; Ran Yan; Dazhong Liu; Huiru Jia; Xiaokang Li; Xinzhu Cang; Yaobin Lv; Kongming Wu (Journal of Pest Science, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Strip application of organic fertilizer in the root zone increases the substitution ratio of chemical nitrogen and sunflower yield in saline-alkali soil - Ran LI; Shujuan WANG; Jia LIU; Erzhen LI; Junxia MIAO; Xiaoliang WEN; Jing YANG; Lizhen XU; Binrui LI; Cunwang JIN; Yan LI; Yonggan ZHAO (Pedosphere, 2025)

Comparison of the effects of three different fungal laccases on the quality of rye bread - Peng Zhou; Ran Zhang; Yuan Gao; Jiaxin Guan; Zifan Chen; Yan Zhang; Ying Li; Guilan Zhu; Wei Wang; Lulu Zhou; Jun Li; Jingjing Wang; et al. (Food Chemistry, 2025)

An air balancing method for ventilation systems considering random fluctuations: Flow prediction and operating condition optimization - Yi Wang; Ran Gao; Yan Tian; Ruoyin Jing; Mengchao Liu; Angui Li (Building and Environment, 2025)

Rock moisture dynamics in sandstone caves responsible for weathering: Field observations and numerical modeling - Ran Niu; Xiao-Wei Jiang; Kaigao Ouyang; Xi Yang; Xu-Sheng Wang; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

An in-situ gold growth self-catalytic signal amplification system enhanced hollow gold immunochromatography for ultrasensitive detection of p24 antigen in HIV infection - Chuanjiang Ran; Qingjie Zhang; Zhenglin Long; Yuhao Li; Xinyue He; Shengzhou Li; Chen Chen; Cong Cheng; Ying Xu; Wenli Zhang; Wei Guo; Yan Shen (Chemical Engineering Journal, 2025)

PM2.5 and microbial aerosols in cold climates: Biological and chemical characteristics, correlation, and source identification during the heating period - Ran Chen; Lili Li; Likun Huang; Guangzhi Wang; Yan Wang (Process Safety and Environmental Protection, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Multi-Omics Investigation of Fatty Acid Content Variations in Common Carp (Cyprinus carpio) Muscle: Integrating Genome, Transcriptome, and Lipid Profiling Data - Kaikuo Wang; Qi Wang; Yingjie Chen; Yiming Cao; Ran Zhao; Shuangting Yu; Xiaoqing Sun; Yan Zhang; Jiongtang Li (Fishes, 2025)
Fatty acids (FAs), especially the polyunsaturated fatty acids (PUFAs), play pivotal roles in growth and development. Fish possess a remarkable ability to synthesize PUFAs, rendering them a crucial and significant source of these essential FAs for human consumption. Despite extensive research on the metabolic processes of FAs, the primary processes underlying FA content variation and corresponding regulatory mechanisms remain largely unexplored. We quantified the muscular FA profiles of 304 common carp samples. High variation in muscle FA content among samples was observed, with the coefficients of variation ranging from 0.36 to 0.92. With genome-wide association studies (GWAS), we identified 1410 SNPs significantly associated with the FA content. The genetic variation at genes participating in oxidation, ubiquitination, and transcriptional factors was associated with the content of multiple FAs, while few variants were observed in the FA-synthesis genes. For the total PUFA (TPUFA) content, transcriptome analysis of groups with the highest and lowest TPUFA content identified 715 differentially expressed genes (DEGs), including genes involved in oxidation and ubiquitination. Using multiple genomic selection programs with the associated SNPs for FA content, we obtained high and positive correlations ranging from 0.65 to 0.92 between the real FA contents and estimated breeding values. These findings manifested the major-effect processes governing the differences in muscular FA content and their regulatory mechanisms. The optimal genomic selection programs provide novel and feasible perspectives to enhance FA content in common carp.

MMFINet: A multimodal fusion network for accurate fish feeding intensity assessment in recirculating aquaculture systems - Xiaoyi Gu; Shili Zhao; Yuqing Duan; Yan Meng; Daoliang Li; Ran Zhao (Computers and Electronics in Agriculture, 2025)

Study on the improvement of Rye bread quality by bacterial Laccase derived from Streptomyces coelicolor - Ran Zhang; Yanhua Li; Yuan Gao; Fengyun Wang; Peng Zhou; Yan Zhang; Ying Li; Kaiyue Wang; Ting Rui; Guilan Zhu; Jingjing Wang; Zemin Fang (Journal of Cereal Science, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Pore microstructure and mass transfer dynamics in thick electrodes for high energy density lithium-ion batteries - Bowei Li; Shanfeng Wang; Pan He; Zhenyao Huang; Bo Mai; Xia Zhang; Yuhang Chen; Yuehua Wen; Xiaqing Ran; Chunhua Han; Ingo Manke; Kang Dong; et al. (Chemical Engineering Journal, 2025)

Nitrate ameliorates myelin loss and cognitive impairment in Alzheimer’s disease through upregulation of neuronal sialin and subsequent inhibition of TPPP phosphorylation - Xinyue Chen; Geng Hu; Lirong Chang; Xiaoyu Li; Yi Tang; Yan Wu; Ran Zhang; Chunmei Zhang; Jinsong Wang; Xue Wang; Songlin Wang (Science Bulletin, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Quantitative source apportionment and health risk assessment for polycyclic aromatic hydrocarbon and their derivatives in indoor dust from housing and public buildings of a mega-city in China - Jijie Kong; Sirui Yan; Xiaoyu Cao; Yuteng Zhang; Chengling Ran; Xianxian Chen; Shaogui Yang; Shiyin Li; Limin Zhang; Huan He (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Buoy-based monitoring of sea surface carbon dioxide partial pressure at Qingdao coastal area - Lu Cao; Su Li; Shuwei Zhang; Ning Wu; Keke Zhang; Wenqing Li; Ran Ma; Dongzhi Chu; Ni Wang; Yan Liu (Frontiers in Marine Science, 2025)
Continuous time series observations of seawater carbon dioxide partial pressure ( p CO 2 ) are crucial for documenting temporal variations in air-sea CO 2 fluxes. To examine the seawater p CO 2 variation and its influence factors at Qingdao coastal waters, a high-resolution observation of seawater p CO 2 near the Xiaomaidao Island was conducted from May 29 to July 25 in 2024. Sea surface p CO 2 varied from 519 µatm to 717 µatm during this monitoring period, with an obvious decline and rise from July 12 to 21. The variation of seawater p CO 2 was mainly affected by the increasing sea surface temperature, except for the period of p CO 2 decrease which was caused by Ulva prolifera bloom. Accompanied by the increase of U. prolifera , sea surface p CO 2 decreased to 563 µatm, then the coverage of U. prolifera decreased and sea surface p CO 2 rose to 669 µatm during period of July 12 to 21. The observation site acted as a source for atmospheric CO 2 throughout the monitoring period, with air-sea CO 2 flux ranging from less than 1 mmol m -2 d -1 to over 100 mmol m -2 d -1 , resulting in a total CO 2 release of 334 mmol m -2 . Thus, it is essential for high-resolution measurement of p CO 2 in coastal areas.

Transcriptome analysis reveals the dynamics of gene expression during early embryonic development of hybrid groupers - Fengying Yan; Chongwei Wang; Yuzhi Zhu; Jinhui Wu; JiayuYang; Songyong Gan; Hao Ran Lin; Yong Zhang; Shuisheng Li (Aquaculture, 2025)

Enhancing groundwater remediation efficiency through integrating Pump-and-Treat system and groundwater circulation well - Zaiyong Zhang; Bin Ran; Chengcheng Gong; Ni Yan; Jingbo Yang; Chunqiang Shen; Yu-Li Wang (Process Safety and Environmental Protection, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

A method for demand controlled ventilation based on a pressure loss model under conditions of non-fully developed flow - Yi Wang; Ran Gao; Mengchao Liu; Angui Li; Yan Tian; Ruoyin Jing (Building and Environment, 2025)

Topology optimization of bend for reducing the local resistance in a piping and duct system - Yan Tian; Ran Gao; Ruoyin Jing; Yi Wang; Angui Li; Xin Dong; Xinpeng Hao; Zheng Ji (Building and Environment, 2025)

Carbon storage potential and influencing factors of mangrove plantation in Kaozhouyang, Guangdong Province, South China - Li Kang; Huang Huamei; Yan Ran; Zhang Shengpeng; Dong Di; Peng Bo (Frontiers in Marine Science, 2025)
Mangrove plantation is a fundamental approach for the sustainable management of tropical and subtropical coasts to capture and store atmospheric carbon. However, it is unknown whether the carbon accumulation potential of planted mangroves is as much as that of natural mangroves. Moreover, the effects of tree species, forest age, and hydrodynamic conditions on carbon storage are still unclear. This study investigated the carbon storage potential and influencing factors for planted mangroves in Kaozhouyang, Huidong County, Guangdong Province. The Vegetation carbon stock was calculated by community parameters collected from field investigation, and ecosystem carbon stock was calculated by the sum of vegetation and sediment. The results showed that mangrove plantation significantly increased the carbon stock of the vegetation and soil (vegetation carbon stock = 9.9645.06 t C/ha; soil carbon stock = 70.37-110.64 t C/ha) compared with the nonvegetation mudflat (63.73 t C/ha). However, the ecosystem carbon stock of the planting sites was still lower than that of natural Avicennia marina (282.86 t C/ha), with the significant difference mainly reflected on the soil carbon stock (p < 0.05). Further results revealed that carbon accumulation was affected by forest age, tree species, and tidal level. The vegetation biomass/carbon stock gradually increased with forest age (p < 0.05), but the difference was not significant for soil carbon stock, which indicated that the carbon accumulation was mainly concentrated on the vegetation at the early stage of mangrove restoration. In addition, suitable habitat conditions (landward) and fast-growing species ( Sonneratia apetala ) are more beneficial to carbon accumulation. Our results suggest that mangrove plantations can achieve carbon storage and sequestration in vegetation and soil for increasing carbon sinks with suitable species selection and management.

Self-catalytic enhancement of Cu-EDTA decomplexation and simultaneous Cu recovery via a dual-cathode electrochemical process - Ran Mao; Ke Hu; Hongshuai Kan; Li Yan; Rongsen Chen; Xu Zhao (Water Research, 2025)

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Enhancing multi-GNSS positioning performances in harsh environments via a refined joint troposphere-multipath hemispherical map - Ran Lu; Mingyuan Zhang; Peng Yuan; Zhao Li; Wen Chen; Miaomiao Cai; Yan Chen; Danan Dong; Weiping Jiang (GPS Solutions, 2025)

A green and effective glucoside surfactant assisted micellar electrokinetic chromatography for the separation of phenolic compounds from medicinal plant using response surface methodology - Qian-Xue Shen; Yan-Hua Jiao; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Preparation and structural characterization of selenium nanoparticles from Lactobacillus reuteri and their protective effects on DSS-induced ulcerative colitis in mice - Li Sun; Si-meng Liu; Yan Ding; Ran Yang; Hua-jin Zeng (Food Bioscience, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

The interplay between dietary flavonoids and gut microbiota in protecting against heart failure - Jieqiong Zhao; Zhongchao Gai; Juan Zhang; Ran Zhao; Xiaoli Liu; Yan Li (Trends in Food Science & Technology, 2024)

Investigation of the self-propulsion performance of a submarine with a pump-jet propulsor in a surface wave–current coupling environment - Yun Ding; Xin-ran Li; Yan Yan; Wen-Quan Wang (Ocean Engineering, 2024)

Accumulation and depuration of 4,5-dihydro-KmTx2 from Karlodinium veneficum in the bivalves, Mercenaria mercenaria and Sinonovacula constricta - Yanrong Li; Rong Chen; Zhujun Zhu; Tong Mu; Zhaoshou Ran; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2024)

Mitigating interfacial recombination enabling efficient semitransparent organic photovoltaics - Hailin Yu; Jiayu Wang; Yuanhao Li; Tianyu Liu; Yufei Gong; Cenqi Yan; Qichao Ran; Qun Luo; Zupan Mao; Xin Wei; Lei Meng; Changqi Ma; et al. (Chemical Engineering Journal, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

The nexus between clean energy market risk and US business environment: evidence from wavelet coherence and variance analysis - Ming Li; Cem Işık; Jiale Yan; Ran Wu (Stochastic Environmental Research and Risk Assessment, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Effects of light spectra on growth and compositions of biomass, fatty acids, and pigments in three typical microalgae from different phyla - Fei Kong; Jiaxing Zhang; Dongzi Yang; Yao Zhou; Yanrong Li; Deshui Chen; Xiaojun Yan; Zhaoshou Ran; Jilin Xu (Journal of Oceanology and Limnology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Visible carbon emissions vs. invisible value-added: Re-evaluating the emissions responsibility of multinational enterprises in global value chains - Yunfeng Yan; Xiyuan Li; Ran Wang; Bo Meng; Zhongxiu Zhao; Xuemeng Li (Ecological Economics, 2024)

Role of ROS signaling in the plant defense against vascular pathogens - Ran Wang; Jianwei Li; Yan Liang (Current Opinion in Plant Biology, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Combustion chemical reaction mechanism and kinetic analysis of RP-3 aviation kerosene/low carbon alcohol blends - Shengli Wei; Yuhan Li; Lirong Wu; Zhicheng Zhang; Shuzhe Yan; Wenjiang Ran (Journal of Cleaner Production, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Autophagy aggravates multi-walled carbon nanotube-induced ferroptosis by suppressing PGC-1 dependent-mitochondrial biogenesis in lung epithelial cells - Lin Zhu; Deyu Zhu; Jiahui Ran; Maojie Li; Zhebin Lai; Yan Zhou; Lei Luo; Xiliang Liu; Kanmin Mao; Kunming Tian (Chemico-Biological Interactions, 2024)

Clinical characteristics and logistic regression analysis of macrolide-resistant Mycoplasma pneumoniae pneumonia in children - Mengzhen Yan; Ran Tao; Shigang Li; Jinwen Xiong; Jinbo Xiang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Sedimentary architecture of a sandy braided river with seasonal hydrodynamic variations: insights from the Permian Lower Shihezi Formation, Ordos Basin, China - Xiaohui Li; Yuliang Su; Guanglei Ren; Feixiang Gao; Shuhong Yan; Huachao Sun; Hui Ran; Mengdi Cui (Frontiers of Earth Science, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Effect of soybean proteins and peptides on the growth and adhesive ability of Limosilactobacillus Reuteri DSM17938 - Yan Wang; Jingyi Wang; Yanchao Wen; Yinxiao Zhang; Ran Wang; Yuan Liu; He Li; Yan Li; Chi Zhang (Archives of Microbiology, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Three episodes of Triassic volcanism in the Eastern Kunlun Orogen, NW China: constraints for evolution of the Palaeo-Tethys Ocean - Hao-Ran Li; Jian-Feng Qiao; Feng-Yue Sun; Ye Qian; Yan-Zhang Wang; Shahzad Bakht; Hao-Tian Liu; Yan Gu (International Geology Review, 2024)

Enhanced interfacial effect via acid theory with boosted photocatalytic performance of nitenpyram removal - Ran Chen; Bo Xu; Heping Cheng; Qianqian Fang; Minghai Ma; Liping Qian; Shunli Wan; Shengyou Xu; Yan Li; Lei Zhang; Shikai Xiang (Chemosphere, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

Advancing rehabilitation: Knittable fiber-shaped sensors for monitoring rotator cuff injury recovery - Han Zhang; Guang Li; Huidan Wei; Xuechen Wu; Sai Yan; Yuhan Xia; Shengyuan Yang; Patrik Schmuki; Ran Cao; Meifang Zhu (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Novel insights into the co-metabolism of pyridine with different carbon substrates: Performance, metabolism pathway and microbial community - Yanyan Fan; Dengke Yan; Xiaolei Chen; Xiaoni Ran; Wang Cao; Haisong Li; Junfeng Wan (Journal of Hazardous Materials, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

LSTM time series NDVI prediction method incorporating climate elements: A case study of Yellow River Basin, China - Yan Guo; Lifeng Zhang; Yi He; Shengpeng Cao; Hongzhe Li; Ling Ran; Yujie Ding; Mikalai Filonchyk (Journal of Hydrology, 2024)

Insights into the long-term immobilization performances and mechanisms of CMC-Fe0/FeS with different sulfur sources for uranium under anoxic and oxic aging - Qi Fang; Yanling Tan; Ran Yan; De Zhang; Mi Li; Xiaoyan Wu; Yilong Hua; Wenjing Xue; Rongzhong Wang (Journal of Environmental Management, 2024)

Deeply analyzing dynamic fermentation of highland barley vinegar: Main physicochemical factors, key flavors, and dominate microorganisms - Yan Li; Aixia Wang; Bin Dang; Xijuan Yang; Mengzi Nie; Zhiying Chen; Ran Lin; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Construction of multiple channels for electron transport in In2S3/In2O3/rGO heterojunctions to boost photocatalytic CO2 conversion to C2+ hydrocarbons - Yipin Zhang; Wenjuan Li; Fu Tian; Na Cai; Qinhui Guan; Dapeng Zhang; Weiguang Ran; Na Li; Tingjiang Yan (Chemical Engineering Journal, 2023)

Pectolinarigenin attenuates hepatic ischemia/reperfusion injury via activation of the PI3K/AKT/Nrf2 signaling pathway - Hao Li; Yabin Chen; Mingjie Ding; Zhiping Yan; Wenzhi Guo; Ran Guo (Chemico-Biological Interactions, 2023)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Construction and evaluation of a phospholipid-based phase transition in situ gel system for brexpiprazole - Ran Tao; Li Liu; Yingxin Xiong; Qianyu Zhang; Xiangyu Lv; Linbo He; Fang Ren; Lu Zhou; Baoyan Chen; Kexin Wu; Yan Zhang; Huali Chen (Drug Delivery and Translational Research, 2023)

Impact of aging-related consumption trend on carbon emission efficiency in China: mediation effect model based on industrial structure adjustment - Ran Yu; Zhangchi Wang; Yan Li (Environmental Science and Pollution Research, 2023)
With the deepening of China’s aging process, changes in the age structure of the population affect the industrial structure and consumption structure in different ways and have a knock-on effect on the whole economic system. Therefore, aging is one of the objective factors affecting future carbon emissions in China. This study analyzes the impact mechanism of aging-related consumption trend on carbon emission efficiency (CEE) based on panel data of 30 Chinese provinces from 2000 to 2019. The results show that the aging-related consumption trend is conducive to the improvement of regional CEE, and the mediation transmission mechanism of industrial structure adjustment is obvious, with a coefficient of 0.1496. The core industry closely linked to the demand for aging-related consumption is consumer services. The promotion of the consumption demand of the aging in the eastern region on the CEE and the transmission stimulation of the industrial structure adjustment are the most obvious. The mediation effect in the central and western regions is relatively weak, and the aging-related consumption demand has not formed a positive interaction with the aging industry. Therefore, improving the market construction of products and services for the aging is beneficial to achieve a virtuous cycle of aging-related consumption upgrading and carbon emission efficiency. This research can provide insights for China to promote industrial structure transformation within the aging trend and also help China meet its carbon neutrality target on schedule.

Evolution of groundwater ecosystem service value in the receiving areas of Beijing-Tianjin-Hebei around the opening of the Middle Route Project of South-to-North Water Diversion - Jihong Qu; Jueyan Jiang; Tiangang Yan; Yuepeng Li; Ran Tian; Liuyue Wang (Acta Geophysica, 2023)

Greening the concrete jungle: Unveiling the co-mitigation of greenspace configuration on PM2.5 and land surface temperature with explanatory machine learning - Yan Li; Yecheng Zhang; Qilin Wu; Ran Xue; Xiaoran Wang; Menglin Si; Yuyang Zhang (Urban Forestry & Urban Greening, 2023)

In-situ grown a zeolitic imidazolate framework for boosting sensitivity of breathable wearable electronics - Guang Li; Han Zhang; Sai Yan; Hengxue Xiang; Huidan Wei; Yuhan Xia; Xunda Feng; Ran Cao; Meifang Zhu (Chemical Engineering Journal, 2023)

Low-resistance local components design method based on topology optimization: A case study of a duct tee - Yan Tian; Ran Gao; Mengchao Liu; Angui Li; Xin Dong; Shengrui Yu; Xiaojie Xie; Tong Li; Pengfei Si (Building and Environment, 2023)

The effects of environmental empathy and sustainable intelligence on wetland tourists’ revisit intention using an extended model of goal-directed behavior - Guoyi Chen; Mingxuan Zou; Ning Ran; Bangquan Yan; Shangkang Li (Journal of Cleaner Production, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Multiplexed detection of biomarkers using a microfluidic chip integrated with mass-producible micropillar array electrodes - Chaozhan Chen; Bin Ran; Bo Liu; Xiaoxuan Liu; Ziteng Zhang; Yan Li; Hongchun Li; Minbo Lan; Yonggang Zhu (Analytica Chimica Acta, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

Experimental study of boiling heat transfer characteristics of metal foam porous-wall mini-channels - Guodong Xia; Yacheng Wang; Ran Li; Ziheng Yan; Qi Li (International Journal of Refrigeration, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Terrigenous organic carbon contributes to reservoir carbon emissions: Potential role of the microbial community along a trophic gradient - Qiong Tang; Lunhui Lu; Fang Luo; Xinrui Li; Yuanyuan Zhang; Ran Li; Carolina Bernal; Solange Vera; Irina Izaguirre; Yan Xiao; Zhe Li (Journal of Hydrology, 2023)

Changes in biochemical metabolites in manila clam after a temporary culture with high-quality microalgal feed mixed with the dinoflagellate species Karlodinium veneficum and K. zhouanum - Yuanbo Pan; Ran Meng; Yanrong Li; Ling Yang; Limin Mei; Yanhua Wu; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2023)

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Improving flavor, bioactivity, and changing metabolic profiles of goji juice by selected lactic acid bacteria fermentation - Wenhui Duan; Qijie Guan; Hui-Ling Zhang; Fang-Zhou Wang; Ran Lu; De-Mao Li; Yan Geng; Zheng-Hong Xu (Food Chemistry, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Flow-Induced Motion and Energy Conversion of the Cir-T-Att Oscillator in a Flow Field with a High Reynolds Number - Danjie Ran; Jijian Lian; Xiang Yan; Fang Liu; Nan Shao; Xu Yang; Lingfan Li (Journal of Marine Science and Engineering, 2023)
The present study aims to systematically investigate the effects of a high Reynolds number on the flow-induced motion and energy conversion of the Cir-T-Att oscillator. Experiments are conducted in six Reynolds number ranges (2.89 × 104~6.51 × 104

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

Recognition of microplastics suspended in seawater via refractive index by Mueller matrix polarimetry - Jiajin Li; Hongyuan Liu; Ran Liao; Hongjian Wang; Yan Chen; Jing Xiang; Xiangrong Xu; Hui Ma (Marine Pollution Bulletin, 2023)

Composite lining-ground interaction behavior in a cold-region circular tunnel under isotropic frost heave action - Hongwei Li; Yuanming Lai; Huyuan Zhang; Yanyan Chen; Wangtao Jiang; Yan Tian; Jiachuan Ran (Cold Regions Science and Technology, 2023)

Soil Carbon Emission Sources Differ Under Litter and Nutrient Addition During Secondary Succession: Evidence from a Mesocosm Study Using a Three-Transfer-Pool Model - Tiantian Li; Cuijuan Liao; Chao Wang; Weiming Yan; Ran Sun; Yangquanwei Zhong (Journal of Soil Science and Plant Nutrition, 2023)

Biosynthesis of LC-PUFA in Ruditapes philippinarum: Cloning and tissue distribution of Fad and Elovl, and effects of microalgae diets varied in LC-PUFA composition on their expressions and fatty acids profile of this bivalve - Kaibin Wu; Zhaoshou Ran; Shurong Wu; Haixuan Xie; Yanrong Li; Kai Liao; Jilin Xu; Xiaojun Yan (Frontiers in Marine Science, 2023)
To reveal the biosynthetic pathway of long-chain polyunsaturated fatty acids (LC-PUFA) in Ruditapes philippinarum , herein, two fatty acid desaturases (Fads, including one Δ5 Fad and one Δ6 Fad-like) and three elongases of very long-chain fatty acids (Elovls, including one Elovl2/5 and two Elovl4-like) genes were firstly cloned from this bivalve and their tissue distributions were examined. Results showed that the newly cloned Fads and Elovls contained the corresponding conserved functional domains and clustered closely with their orthologs, respectively. Meanwhile, they were expressed significantly higher in the digestive glands and intestine. Subsequently, to further understand the LC-PUFA biosynthesis in R. philippinarum , the effects of dietary LC-PUFA on Fad and Elovl expressions and the fatty acid (FA) profile in this bivalve were investigated by feeding with three microalgae varied in LC-PUFA compositions [including Chlorella sp. (rich in 18:2n-6 and 18:3n-3), Chaetoceros calcitrans (rich in eicosapentaenoic acid, EPA), and Isochrysis galbana (rich in docosahexaenoic acid, DHA]. Results showed that, throughout the experiment, the expressions of Fad and Elovl were significantly up-regulated in the visceral mass (digestive glands and intestine) of R. philippinarum fed with Chlorella sp., while no significant changes or slightly decreases were observed in those fed with I. galbana . Furthermore, in those fed with C. calcitrans , the expressions of Fad were not significantly changed, whereas the expressions of Elovl were firstly up-regulated but then restored to its initial level at the end of experiment. These results suggested that R. philippinarum could modulate Fad and Elovl expressions to adapt to the dietary LC-PUFA composition. The FA analysis showed that a significantly higher amount of DHA and EPA was found in the R. philippinarum fed with I. galbana and C. calcitrans , respectively, which reflected well of the dietary FA. However, the R. philippinarum fed with Chlorella sp. exhibited a significant decrease of 18:2n-6 and 18:3n-3 but with a significant increase of their products such as 20:3n-6 and 22:5n-3, indicating that R. philippinarum had a certain capacity for LC-PUFA biosynthesis. Collectively, this study provided valuable insights into the biosynthesis of LC-PUFA in R. philippinarum .

Transition metal tuned g-C3N4 induce highly efficient photocatalytic of ammonia borane to hydrogen evolution and mechanism investigation - Ruiming Fang; Zhongqing Yang; Ziqi Wang; Mingnv Guo; Yunfei Yan; Jingyu Ran; Li Zhang (Fuel, 2023)

Reducing the computational load – atomic multiconfiguration calculations based on configuration state function generators - Yan Ting Li; Kai Wang; Ran Si; Michel Godefroid; Gediminas Gaigalas; Chong Yang Chen; Per Jönsson (Computer Physics Communications, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

A novel microseismic classification model based on bimodal neurons in an artificial neural network - Chunchi Ma; Hang Zhang; Xiangqian Lu; Xiang Ji; Tianbin Li; Yong Fang; Wenjin Yan; Xuefeng Ran (Tunnelling and Underground Space Technology, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Collagen-anchored cascade nanoreactors with prolonged intratumoral retention for combined cancer starvation and chemotherapy - Jingqing Mu; Yuyuan Du; Xingwei Li; Ran Yan; Haiping Zhong; Maoyu Cai; Na Yu; Jinchao Zhang; Xiaoyong Yuan; Xia Hua; Shutao Guo (Chemical Engineering Journal, 2023)

Associations of exposure to multiple metals with the risk of age-related cataract in Anhui, China: a case–control study - Yan-Qing Li; Qian Wang; Ran Liu; Guo-Ao Li; Jia-Liu He; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Sea ice recognition for CFOSAT SWIM at multiple small incidence angles in the Arctic - Meijie Liu; Ran Yan; Xi Zhang; Ying Xu; Ping Chen; Yongsen Zhao; Yuexiang Guo; Yangeng Chen; Xiaohan Zhang; Shengxu Li (Frontiers in Marine Science, 2022)
Sea ice recognition is one of the main tasks for sea ice monitoring in the Arctic and is also applied for the detection of other ocean phenomena. The Surface Wave Investigation and Monitoring (SWIM) instrument, as an innovative remote sensor that operates at multiple small incidence angles, is different from existing sensors with moderate and normal incidence modes for sea ice monitoring. Sea ice recognition at small incidence angles has rarely been studied. Moreover, SWIM uses a discrimination flag of sea ice and sea water to remove sea ice from sea wave products. Therefore, this research focuses on sea ice recognition in the Arctic based on SWIM data from October 2020 to April 2021. Eleven features are first extracted, and applied for the analysis of the waveform characteristics using the cumulative probability distribution (CPD) and mutual information measurement (MIM). Then, random forest (RF), k-nearest neighbor (KNN) and support vector machine (SVM) classifiers are built, and their abilities of sea ice recognition are assessed. The optimal classifier is the KNN method with Euclidean distance and k equal to 11. Feature combinations are also used to separate sea ice and sea water based on the KNN method to select the optimal combination. Thus, the optimal classifier-feature assembly at each small incidence angle is established, and the highest overall accuracy reaches 97.1%. Moreover, the application of the optimal classifier–feature assemblies is studied, and its performance is fairly good. These assemblies yield high accuracies in the short- and long-term periods of sea ice recognition, and the overall accuracies are greater than 93.1%. So, the proposed method satisfies the SWIM requirement of removing the sea ice effect. Moreover, sea ice extents and edges can be extracted from SWIM sea ice recognition results at a high level of precision greater than 94.8%. As a result, the optimal classifier–feature assemblies based on SWIM data express the effectiveness of the SWIM approach in sea ice recognition. Our work not only highlights the new sea ice monitoring technology of remote sensing at small incidence angles, but also studies the application of SWIM data in sea ice services.

Ectomycorrhizal synthesis between two Tuber species and six tree species: are different host-fungus combinations having dissimilar impacts on host plant growth? - Lan-Lan Huang; Yan-Liang Wang; Alexis Guerin-Laguette; Ran Wang; Peng Zhang; Yong-Mei Li; Fu-Qiang Yu (Mycorrhiza, 2022)

Whole-transcriptome sequencing identifies key mRNAs, miRNAs, lncRNAs, and circRNAs associated with unexplained recurrent pregnancy loss - Yan Wang; Qing Cheng; Zhengyi Xia; Ran Zhou; Yiming Li; Lulu Meng; Qing Xu; Jianxin Tan; Zhengfeng Xu (Cell and Tissue Research, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Core fucosylation of maternal milk N-glycan prevents intestinal inflammation by regulating Treg/Th17 balance in infant gut microbiota - Jia Tao; Yan Ran; Zhongmin Pan; Li Wang (Molecular & Cellular Toxicology, 2022)

Editing arcs to improve the capacity of GNSS-IR for soil moisture retrieval in undulating terrains - Qishun Ran; Bao Zhang; Yibin Yao; Xiao Yan; Junyu Li (GPS Solutions, 2022)

Energy structure, digital economy, and carbon emissions: evidence from China - Yan Li; Xiaodong Yang; Qiying Ran; Haitao Wu; Muhammad Irfan; Munir Ahmad (Environmental Science and Pollution Research, 2021)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Evaluation and improvement of the greenness of plasma spraying through life cycle assessment and grey relational analysis - Jing Liu; Liming Wang; Fangyi Li; Yanle Li; Xueju Ran; Lin Kong; Yan Fu (The International Journal of Life Cycle Assessment, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Genome-wide linkage mapping for canopy activity related traits using three RIL populations in bread wheat - Faji Li; Weie Wen; Jindong Liu; Shengnan Zhai; Xinyou Cao; Cheng Liu; Dungong Cheng; Jun Guo; Yan Zi; Ran Han; Xiaolu Wang; Aifeng Liu; et al. (Euphytica, 2021)

Transcriptome sequencing and analysis for the pigmentation of scale and skin in common carp (Cyprinus carpio) - Yu-Jie Zhao; Jun Xiao; Mei-Di Huangyang; Ran Zhao; Qi Wang; Yan Zhang; Jiong-Tang Li (Molecular Biology Reports, 2021)

Whole-genome resequencing reveals loci with allelic transmission ratio distortion in F1 chicken population - Peng Ren; Feilong Deng; Shiyi Chen; Jinshan Ran; Jingjing Li; Lingqian Yin; Yan Wang; Huadong Yin; Qing Zhu; Yiping Liu (Molecular Genetics and Genomics, 2021)

Complete genome sequence of citrus yellow spot virus, a newly discovered member of the family Betaflexiviridae - Zhiyou Xuan; Shuai Li; Song Zhang; Wenyi Ran; Yan Zhou; Fangyun Yang; Changyong Zhou; Mengji Cao (Archives of Virology, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Building a sequence map of the pig pan-genome from multiple de novo assemblies and Hi-C data - Xiaomeng Tian; Ran Li; Weiwei Fu; Yan Li; Xihong Wang; Ming Li; Duo Du; Qianzi Tang; Yudong Cai; Yiming Long; Yue Zhao; Mingzhou Li; et al. (Science China Life Sciences, 2020)

Herbaceous layer determines the relationship between soil respiration and photosynthesis in a shrub-dominated desert plant community - Jie Ma; Ran Liu; Chenhua Li; Lianlian Fan; Guiqing Xu; Yan Li (Plant and Soil, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Bioactive compounds from Cudrania tricuspidata: A natural anticancer source - Xusheng Li; Zilan Yao; Xinwei Jiang; Jianxia Sun; Guojing Ran; Xuan Yang; Yaqi Zhao; Ying Yan; Zisheng Chen; Lingmin Tian; Weibin Bai (Critical Reviews in Food Science and Nutrition, 2020)

Seasonal variation in the groundwater dependency of two dominant woody species in a desert region of Central Asia - Xue Wu; Xin-Jun Zheng; Xin-Wei Yin; Yue-Meng Yue; Ran Liu; Gui-Qing Xu; Yan Li (Plant and Soil, 2019)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Modeling the late Pliocene global monsoon response to individual boundary conditions - Ran Zhang; Dabang Jiang; Zhongshi Zhang; Qing Yan; Xiangyu Li (Climate Dynamics, 2019)

Nuclear localization signal in TRIM22 is essential for inhibition of type 2 porcine reproductive and respiratory syndrome virus replication in MARC-145 cells - Huiyuan Jing; Ran Tao; Nan Dong; Sufang Cao; Yanting Sun; Wenting Ke; Yang Li; Jinhe Wang; Yan Zhang; Hui Huang; Wang Dong (Virus Genes, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Effect of salinity on volatiles in the razor clam investigated by head space-solid phase microextraction/gas chromatography-mass spectrometry - Zhaoshou Ran; Sijia Zhang; Yilei Zhu; Aiying Ke; Jilin Xu; Yanrong Li; Kai Liao; Shuang Li; Yun Ran; Xiaojun Yan (Fisheries Science, 2019)

Partitioning water source and sinking process of a groundwater-dependent desert plant community - Ran Liu; Yugang Wang; Congjuan Li; Jie Ma; Yan Li (Plant and Soil, 2018)

Metagenomic DNA Extraction of Natural Cellulose-Degrading Consortia - Ran Du; Lvjun Guo; Shizhong Li; Daoxin Xie; Jianbin Yan (BioEnergy Research, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Investigation of Perfluoroalkyl Substances (PFASs) in Sediments from the Urban Lakes of Anqing City, Anhui Province, China - Fasong Li; Hanyu Huang; Zhibing Xu; Hui Ni; Hao Yan; Ran Chen; Yan Luo; Wei Pan; Jinyun Long; Xiaofang Ye; Xiaofen Qian; Guangming Yu (Bulletin of Environmental Contamination and Toxicology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Legacy effects of simulated short-term climate change on ammonia oxidisers, denitrifiers, and nitrous oxide emissions in an acid soil - Xiaoya Xu; Xiaorui Liu; Yong Li; Yu Ran; Yapeng Liu; Qichun Zhang; Zheng Li; Yan He; Jianming Xu; Hongjie Di (Environmental Science and Pollution Research, 2017)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Precipitation Pattern Determines the Inter-annual Variation of Herbaceous Layer and Carbon Fluxes in a Phreatophyte-Dominated Desert Ecosystem - Ran Liu; Ellen Cieraad; Yan Li; Jie Ma (Ecosystems, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Calmodulin kinase II inhibitor regulates calcium homeostasis changes caused by acute β-adrenergic receptor agonist stimulation in mouse ventricular myocytes - Yan Huang; Tao Liu; Dandan Wang; Xin Wang; Ran Li; Yuting Chen; Yanhong Tang; Teng Wang; Congxin Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Enhanced hydroxyl radical generation in the combined ozonation and electrolysis process using carbon nanotubes containing gas diffusion cathode - Donghai Wu; Guanghua Lu; Ran Zhang; Qiuhong Lin; Zhenhua Yan; Jianchao Liu; Yi Li (Environmental Science and Pollution Research, 2015)

Odontoblast β-catenin signaling regulates fenestration of mouse Hertwig’s epithelial root sheath - Ran Zhang; Yan Teng; Liang Zhu; JingTing Lin; Xiao Yang; Guan Yang; TieJun Li (Science China Life Sciences, 2015)

Paenibacillus herberti sp. nov., an endophyte isolated from Herbertus sendtneri - Guan Nan Guo; Xun Zhou; Ran Zhao; Xin Yao Chen; Zhi Ling Chen; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Mid-Pliocene westerlies from PlioMIP simulations - Xiangyu Li; Dabang Jiang; Zhongshi Zhang; Ran Zhang; Zhiping Tian; Qing Yan (Advances in Atmospheric Sciences, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Response of vacuolar processing enzyme in Malus hupehensis and MhVPEγ-overexpressing Arabidopsis to high temperature stress - Qian Su; Kun Ran; Xiu-Jin Men; Wei-Wei Zhang; Shu-Lei Fan; Li-Juan Yan; Hong-Qiang Yang (Acta Physiologiae Plantarum, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Chryseobacterium polytrichastri sp. nov., isolated from a moss (Polytrichastrum formosum), and emended description of the genus Chryseobacterium - Xin Yao Chen; Ran Zhao; Zhi Ling Chen; Lei Liu; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

Long non-coding RNAs: new players in ocular neovascularization - Xue-Dong Xu; Ke-Ran Li; Xiu-Miao Li; Jin Yao; Jiang Qin; Biao Yan (Molecular Biology Reports, 2014)

Cloning and analysis of a functional promoter of fungal immunomodulatory protein from Flammulina velutipes - Wei-Ran Cong; Yan Liu; Qi-Zhang Li; Xuan-Wei Zhou (Molecular Biology Reports, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Summer rain pulses may stimulate a CO2 release rather than absorption in desert halophyte communities - Ran Liu; Ellen Cieraad; Yan Li (Plant and Soil, 2013)

Spectroscopic exploring the affinities, characteristics, and mode of binding interaction of curcumin with DNA - Xiao-Ling Li; Yan-Jun Hu; Ran Mi; Xiao-Yun Li; Pei-Qi Li; Yu Ouyang (Molecular Biology Reports, 2013)

Biophysical studies on the interactions of jatrorrhizine with bovine serum albumin by spectroscopic and molecular modeling methods - Ran Mi; Pei-Qi Li; Yan-Jun Hu; Xiao-Yang Fan; Hai-Ying Li; Xue-Cheng Yu; Yu Ouyang (Molecular Biology Reports, 2013)

The biochemical and immunological characterization of two serpins from Clonorchis sinensis - Huali Lei; Yanli Tian; Wenjun Chen; Xiaoyun Wang; Xuerong Li; Qiang Mao; Jiufeng Sun; Ran Li; Yanquan Xu; Chi Liang; Yan Huang; Xinbing Yu (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Molecular identification and characterization of leucine aminopeptidase 2, an excretory-secretory product of Clonorchis sinensis - Chuanhuan Deng; Jiufeng Sun; Xuerong Li; Lexun Wang; Xuchu Hu; Xiaoyun Wang; Wenjun Chen; Xiaoli Lv; Chi Liang; Wenfang Li; Yan Huang; Ran Li; et al. (Molecular Biology Reports, 2012)

Dissipation and Residue Determination of Fluoroglycofen-Ethyl in Soybean and Soil by UPLC-MS–MS - Yue Geng; Ran Jia; Chongjiu Li; Xiaodong Ma; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Gene/protein expression level, immunolocalization and binding characteristics of fatty acid binding protein from Clonorchis sinensis (CsFABP) - Lisi Huang; Yue Hu; Yan Huang; Hang Fang; Ran Li; Dong Hu; Wenfang Li; Xuerong Li; Chi Liang; Xinbing Yu (Molecular and Cellular Biochemistry, 2012)

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Expressions of thermostable bacterial cellulases in tobacco plant - Xi-ran Jiang; Xiao-ya Zhou; Wen-yan Jiang; Xiao-rong Gao; Wen-li Li (Biotechnology Letters, 2011)

Three new fatty acids from the roots of Boehmeria nivea (L.) Gaudich and their antifungal activities - Qiong-Ming Xu; Yan-Li Liu; Xiao-Ran Li; Xia Li; Shi-Lin Yang (Natural Product Research, 2011)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

Molecular cloning, characterization and expression analysis of a new gene encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase from Salvia miltiorrhiza - Pan Liao; Wei Zhou; Lin Zhang; Jing Wang; Xiangming Yan; Yan Zhang; Ran Zhang; Li Li; Genyu Zhou; Guoyin Kai (Acta Physiologiae Plantarum, 2009)

Construction of the Vero cell culture system that can produce infectious HCV particles - Jia Guo; Ran Yan; Guodong Xu; Weiyun Li; Congyi Zheng (Molecular Biology Reports, 2009)

MicroRNA-128 inhibits glioma cells proliferation by targeting transcription factor E2F3a - Yu Zhang; Tengfei Chao; Ran Li; Wei Liu; Yang Chen; Xingqi Yan; Yanhua Gong; Bin Yin; Wei Liu; Boqing Qiang; Jizhong Zhao; Jiangang Yuan; et al. (Journal of Molecular Medicine, 2009)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)